Effects of immersion in 4-methacryloyloxyethyl trimellitate anhydride/methyl methacrylate-tri-n-butyl borane resin-activated liquid on microtensile bond strength of root canal dentin - Taisuke Ozaki; Shiho Otake; Wataru Komada; Shinya Oishi; Kenji Fueki (Journal of Dental Sciences, 2024)
Background/purpose: 4-methacryloyloxyethyl trimellitate anhydride/methyl methacrylate-tri-n-butyl borane (4-META/MMA-TBB) resin is used for indirect restorations. We aimed to evaluate effects of immersion in 4-META/MMA-TBB-activated liquid on the bond strength of root canal dentin. Materials and methods: We used freshly extracted single-rooted human teeth. After decoronation, each root was vertically sectioned into halves; their dentin walls were polished and flattened. The control group underwent dentin treatment with Green Activator. The immersion group was treated with Green Activator and Teeth Primer and immersed in 4-META/MMA-TBB-activated liquid. After bonding the resin blocks with Super-Bond, microtensile bond strength (μTBS) tests were performed (n = 6), and fracture surfaces were analyzed. Before surface treatment, dentin was immersed in a sodium fluorescein solution for 3 h, and resin blocks were bonded with Super-Bond with rhodamine B as in the bond strength test. The bonded cross section was observed using confocal laser scanning microscopy (CLSM). Results: μTBS was significantly higher in the immersion group than in the control group (61.5 [51.3–66.7] vs. 33.0 [20.4–57.8] MPa; P < 0.05). Fracture mode analysis showed that, compared with the control group, the immersion group had a significantly lower rate of adhesive failure at the dentin interface and a significantly higher rate of cohesive failure in Super-Bond (P < 0.01). CLSM showed a water droplet-like accumulation of fluorescein dye above the hybrid layer in the control group, not in the immersion group. Conclusion: Immersion in a 4-META/MMA-TBB-activated liquid inhibited water exudation from the root canal dentin and improved the bond strength.